Igneous Rock Associations 7. Arc Magmatism I:: Relationship Between Subduction and Magma Genesis - Murphy, J. (Geoscience Canada, 2006)
Dehydration of subducted oceanic lithosphere releases fluid into the overlying mantle wedge and initiates a chain of events culminating in the generation of magma that rises to form volcanic arcs. Arc magmas are distinct from magmas in other settings because of the different geothermal regimes at destructive plate margins, the presence of fluids/volatiles derived from dehydration of the subducted slab and the generally compressive tectonic regime that inhibits the ascent of magma, thereby promoting extensive interaction with the adjacent wall rocks. As a result, most arc magmas solidify as intrusive bodies, ranging from sills and dykes to large plutonic complexes. Several mechanisms facilitate the rise of arc magmas. Diapirs rising from a larger pool of buoyant magma are important in the ductile lower crust. The rapid rise and the expansion of magma results in the propagation of fractures, that facilitate stoping and assimilation in the brittle upper crust. Fracture zones are repeatedly exploited, and the net result may be formation of a composite batholith. Water plays an important role in all stages of arc-magma evolution. Water lowers the temperatures that are required for the partial melting in the mantle wedge, which produces mafic magma, and in the crust, produces felsic magma. Arc magmatism is intimately related to metamorphism, although this relationship is complicated largely because maximum pressures and temperatures are attained at different times. Arcs under compression undergo rapid thickening, followed by erosional or tectonic exhumation. Crustal melting is triggered by a variety of processes, including relaxation following crustal thickening. Melting initiates at the base of the crust, but eventually occurs at shallower crustal levels. Arcs under extension have a steep geothermal gradient and underplating of the crust by mafic magma may transfer sufficient heat to induce anatexis. During a prolonged history of subduction, the dip and location of the subduction zone may vary causing the locus of arc magmatism to migrate and causing intermittent switching from compressional to extensional environments.